(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The study analyzes the motivational conditions for the successful implementation of public management decisions: ensuring the legitimate rights and freedoms of citizens, compliance with the rule of law and state interests, compliance with the democratic foundations of the state and the interests of civil society.